2008
DOI: 10.1097/ijg.0b013e31815c5f7c
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cerebrospinal Fluid Pressure in Glaucoma Pathophysiology: The Dark Side of the Optic Disc

Abstract: It is generally accepted that glaucoma occurs when intraocular pressure (IOP) is raised above atmospheric pressure beyond tolerable limits for the optic disc. However, the other, unseen side of the optic disc is not air but a set of pressure compartments dominated by the cerebrospinal fluid (CSF) within the subarachnoid space. This invisibility has made investigation difficult; however, in recent decades there has been increased interest in this corollary to IOP. We briefly review the anatomy of the optic nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 49 publications
7
97
0
3
Order By: Relevance
“…In animal models, one variable that has been shown to be related to structural changes in the ONH similar to the glaucomatous damage is intracranial pressure (ICP) [1]. The literature suggests that pressure gradients between intra-and extra-ocular compartments may be involved in the damage to the retinal ganglion cell's axons that cross the lamina cribosa [2,3]. However, the need for painful and invasive techniques to study ICP, such as lumbar puncture, has deterred most authors from evaluating this variable in the overall glaucoma research field.…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, one variable that has been shown to be related to structural changes in the ONH similar to the glaucomatous damage is intracranial pressure (ICP) [1]. The literature suggests that pressure gradients between intra-and extra-ocular compartments may be involved in the damage to the retinal ganglion cell's axons that cross the lamina cribosa [2,3]. However, the need for painful and invasive techniques to study ICP, such as lumbar puncture, has deterred most authors from evaluating this variable in the overall glaucoma research field.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition the effect of the translaminar pressure gradient on the lamina cribrosa may be important. 6,7 Additional research in this area has focused on humoral abnormalities in patients with OAG. A number of molecules are currently under investigation, such as endothelin-1, 8 vascular endothelial growth factor, 9 tumor necrosis factor-alpha, 10 matrix metalloproteinases, and their inhibitors.…”
mentioning
confidence: 99%
“…15,20 It has been shown that mechanical stress and possible deformation of the LC can have a deleterious effect on axonal functioning. 21,22 Furthermore, anterior displacement of prelaminar tissue following trabeculectomy for OAG has been described in a number of studies with variable results. Patients in these studies were followed up for periods varying from several weeks to 2 years, [1][2][3][4][5] and different patient populations and imaging platforms were used.…”
Section: Discussionmentioning
confidence: 99%